Paddling with the Mississippi River: place-based–but not place-bound–knowledge production - Warren, Natalie (Frontiers in Communication, 2026)
This article explores how sustained embodied experiences in and with environments shape ecological awareness, challenge dominant narratives of nature as passive or separate, and provide new modes of environmental meaning-making. Through an autoethnographic account of my 70-day canoe expedition down the Mississippi River, I investigate how “paddling with” acts as a rhetorical and relational practice—a form of experiential environmental communication that reveals, complicates, and sometimes transforms perceptions of the river. Drawing from Indigenous epistemologies of “walking with,” it offers a framework for understanding how immersive ecological encounters can not only encourage place-based knowledge but also spark ecological thinking. In doing so, it calls for greater scholarly attention to the communicative power of physical encounters with place—particularly as they shape and contest hegemonic narratives of humans and nature to reveal our vast interconnectedness with all life.